30ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF Ammi visnaga EXTRACTS AGAINST PATHOGENIC MICROORGANISMS - Ghareeb, Abdulameer; Zedan, Tamara; Gharb, Lamia’a (Iraqi Journal of Science, 2024)
Antimicrobial activity of ethanolic and aqueous extracts from fruits of commonly used medicinal plant in Iraq Ammi visnaga was evaluated against eight pathogenic microorganisms Staphylococcus aureus, Leuconostic mesontroide, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Candida tropicans and C. albicans over a wide range of concentrations (0.05-50 mg/ml). Minimum inhibition concentration (MIC) and the diameter of inhibition zone (DIZ) were determined by In vitro bioassays using hole-plate diffusion method.The ethanolic and aqueous extract from the fruit part of the plant showed antimicrobial activity against most tested microorganisms. The most active extract against Gram-positive bacteria was ethanol extract with a minimal inhibitory concentration (MIC) value of (5mg/ml) against Enterococcus faecalis. In addition, the same extract from the plant part demonstrated in antimicrobial activity against the Gram-negative bacteria Escherichia coli, Klebsiella pneumoniae with an MIC value of 12.5mg/ml.In yeast it need high concentration of extract to cause inhibition.This study shed the light on the ability of extracts from Ammi visnaga to combat pathogens which will help as natural antimicrobial agents as well as can be used in pharmaceutical and food preservation systems.